Determinants of Economic Growth of Nepal - Didiya, Muraj (Bagiswori Journal, 2024)
The purpose of this paper is to analyse the impact of Foreign Direct Investment (FDI), Exchange Rate (EXR) and Consumer Price Inflation (CPI) to the Gross Domestic Product (GDP) growth in Nepal. Descriptive and causal comparative research designs were used to analyse the impact of FDI, EXR and CPI on economic growth of Nepal. The study has used 17 years' annual time-series data of FDI, GDP at current price, CPI, and EXR throughout the FY 2006/07 to 2022/23 in Nepal. The empirical results found that EXR and FDI have positive and significant impact on the economic growth of Nepal whereas the adverse effect of CPI on economic growth has been found. FDI and favorable EXR appearing as key drivers of economic growth, but rising prices could slow down it.